2021
DOI: 10.1002/cpe.6460
|View full text |Cite
|
Sign up to set email alerts
|

Kullback chi square and Gustafson Kessel probabilistic neural network based soil fertility prediction

Abstract: Agriculture plays a significant role in any country's wealth creation, fulfilling food security needs and employment generation thereby contributing immensely to the country's growth and GDP. However, certain characteristics such as climate and environmental changes have extensively become menacing factors in the agriculture output. As soil is an influential specification influencing the prediction of crop yield, soil analysis becomes imperative and can assist farmers in preliminary adaptations towards better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A supervised ML algorithm is used on training datasets and tested on test datasets, and R Tools is used to execute this algorithm. Rajamanickam & Mani (2021) proposed predicting soil fertility by integrating uncertainty quantification using fisher ratio pre-processing models and Kullback divergent chi-square FS. Then, rather than an individual value, Gustafson-Kessel probabilistic NN classifications use the soil fertility prediction models to generate the likelihood distribution as output and the distinct types of soil fertility levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A supervised ML algorithm is used on training datasets and tested on test datasets, and R Tools is used to execute this algorithm. Rajamanickam & Mani (2021) proposed predicting soil fertility by integrating uncertainty quantification using fisher ratio pre-processing models and Kullback divergent chi-square FS. Then, rather than an individual value, Gustafson-Kessel probabilistic NN classifications use the soil fertility prediction models to generate the likelihood distribution as output and the distinct types of soil fertility levels.…”
Section: Methodsmentioning
confidence: 99%
“…Also, a semi-supervised classification pipeline is introduced that is based on CAE and uses endmember abundance maps as classification features. Real hyperspectral datasets are used for experiments, and supervised and semi-supervised models are used to compare the results ( Rajamanickam & Mani, 2021 ). The layer-wise training is implemented for optimizing parameters of the entire network.…”
Section: Methodsmentioning
confidence: 99%
“…Crop damage from climate change and other environmental stresses on farming methods were discussed in [5] by Rajamanickam and Mani. Higher accuracy and lower processing time are provided by the authors' suggested probabilistic neural network for the soil fertility prediction approach.…”
Section: Literature Surveymentioning
confidence: 99%
“…In [28], Rajamanickam and Mani addressed the impact of climate anomalies on crops and environmental challenges on agriculture practices. The authors have proposed a probabilistic neural network for the soil fertility prediction approach, providing higher accuracy and reduced processing time.…”
Section: Related Workmentioning
confidence: 99%